Numerical Studies of Particle-Gas Two-Phase Flowing through Microshock Tubes - Guang Zhang; Wei Wei Wang; Xiang Hui Su; Xiao Jun Li; Wen Hao Shen; Zhe Lin (Shock and Vibration)
Microshock tubes are always used to induce shock waves and supersonic flows in aerospace and medical engineering fields. A needle-free drug delivery device including a microshock tube and an expanded nozzle is used for delivering solid drug powders through the skin surface without any injectors or pain. Therefore, to improve the performance of needle-free drug delivery devices, it is significantly important to investigate shock waves and particle-gas flows induced by microshock tubes. Even though shock waves and multiphase flows discharged from microshock tubes have been studied for several decades, the characteristics of unsteady particle-gas flows are not well known to date. In the present studies, three microshock tube models were used for numerical simulations. One microshock tube model with closed end was used to observe the reflected shock wave and flow characteristics behind it. The other two models are designed with a supersonic nozzle and a sonic nozzle at the exit of the driven section, respectively, to investigate particle-gas flows induced by different nozzles. Discrete phase method (DPM) was used to simulate unsteady particle-gas flows and the discrete random walk model was chosen to record the unsteady particle tracking. Numerical results were obtained for comparison with those from experimental pressure measurement and particle visualization. Shock wave propagation was observed to agree well with experimental results from numerical simulations. Particles were accelerated at the exit of microshock tube due to the reservoir pressure induced by reflected shock wave. Both sonic and supersonic nozzles were underexpanded at the end of microshock tubes. Particle velocity was calculated to be smaller than gas velocity, which results from larger drag of injected particles.